Hybrid-Trefftz stress and displacement elements for dynamic analysis of bounded and unbounded saturated porous media - Moldovan, Ionut D.; Freitas, Joan A. Teixeira de (Computer Assisted Methods in Engineering and Science; Vol 15 No 3-4 (2008), 2022)
The displacement and stress models of the hybrid-Trefftz finite element formulation are applied to the dynamic analysis of two-dimensional bounded and unbounded saturated porous media problems. The formulation develops from the classical separation of variables in time and space. A finite element approach is used for the discretization in time of the governing differential equations. It leads to a series of uncoupled problems in the space dimension, each of which is subsequently discretized using either the displacement or the stress model of the hybrid-Trefftz finite element formulation. As typical of the Trefftz methods, the domain approximation bases are constrained to satisfy locally all domain equations. An absorbing boundary element is adopted in the extension to the analysis of unbounded media. The paper closes with the illustration of the application of the alternative hybrid-Trefftz stress and displacement elements to the solution of bounded and unbounded consolidation problems.